The Cost Structure of American Research Universities - de Groot, Hans; McMahon, Walter W.; Volkwein, J. Fredericks (The Review of Economics and Statistics, 1991)
This study estimates translog variable cost functions for 147 American doctorate granting universities, accounting for three major products of these institutions: undergraduate and graduate instruction, and research. Explicit measures of research output and quality are employed. Evidence is found for considerable economies of scale for the average institution, as well as economies of scope related to the joint production of undergraduate and graduate instruction. The public or private ownership of an institution is not significant for the explanation of variable costs. The intensity of state regulation in the public sector does not have a significant impact on production efficiency. Copyright 1991 by MIT Press.